STUDI PENGARUH KADAR AIR DAN POROSITAS TERHADAP NILAI KUAT TEKAN UNIAKSIAL BATU ANDESIT DI SAOKA SORONG PROVINSI PAPUA BARAT - Fanila Oktafia A. Kemon; Karmila Laitupa (INTAN Jurnal Penelitian Tambang, 2022)
Rock physical properties such as water content and porosity affect mechanical properties such as the compressive strength value or rock strength value. This parameter is an input parameter for geotechnical or structural design purposes. To understand the effect of water content and porosity on the rock's compressive strength a laboratory test is needed. Rock samples are taken in the form of lumps and then prepared and tested according to predetermined standards. The result is a decrease in water content and a porosity results in an increase in the compressive strength. Based on the correlation value of the original water content = 0.061, saturated water content = 0.001, and porosity = 0.408, it shows a weak influence or relationship. This is due to the water content and porosity having a coefficient of determination or R2 value of less than 0.6.